Perbandingan Konsep Tarbiyah, Ta’lim, dan Ta’dib - Madona Agustin Sari (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Abstract. God's creatures are necessary because to fulfill his responsibilities as a leader on this earth he is none other than humans. Islamic education is one of the platforms that forms Al-Tarbiyah, Al-Ta'dib and also Ta'lim. Of the three things that are often used, namely Tarbiyah, where the word has a meaning whose basic meaning is describing growth, maturity and development, maintaining and adapting as well as supporting education which is defined as an effort to create a broad and very useful source of information. Therefore, the essence of education is to equip humans with good skills and knowledge about shapes and numbers. So being an educator and teaching is essentially a divine function, where the Qur'an emphasizes that Allah is an educator for the universe and an educator for mankind. Developing the personality of students with alternative spiritual, rational, emotional and spiritual training.